Paternal education level and emotional regulation in parental feeding were associated with cognitive performance in a sample of preschoolers in Selangor - Juhari, Nur Amalin; Chin, Yit Siew (Asian Network for Scientific Information, 2019)
This study aimed to determine factors associated with cognitive performance among preschoolers in Selangor. Materials and Methods: A total of 167 preschoolers (80 boys and 87 girls) and their parents from eight selected kindergartens were included in this study. Information on socio-demographic background, children's eating styles and parental feeding practices was provided by parents. A Raven's Coloured Progressive Matrices (R-CPM) was used to assess the cognitive performance of preschoolers. The BMI-for-age (BAZ), height-for-age (HAZ) and weight-for-age (WAZ) of preschoolers were determined based on their measured body weight and height. Results: A majority of the preschoolers attained average cognitive performance levels (95.6±12.1). Bivariate results showed that a high number of parental years of schooling (father: r = 0.154, p<0.05; mother: r = 0.155, p<0.05), a high monthly household income (rs = 0.170, p<0.05), high satiety responsiveness (r = 0.165, p< 0.05) and high emotional regulation in parental feeding (r = 0.170, p<0.05) were associated with better cognitive performance of preschoolers. In multivariate analysis, fathers who attained a higher number of years of schooling (β = 0.155) and parents with higher emotional regulation in parental feeding (β = 0.171) contributed to better cognitive performance among preschoolers. Conclusion: Parents play important roles in improving the cognitive performance of their children. Therefore, parental involvement in future health promotion programs, particularly in feeding practices, is needed to improve the cognitive performance of preschoolers.